2020
DOI: 10.1038/s41586-020-2555-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of stretch-mediated skin expansion at single-cell resolution

Abstract: Data availabilityData associated with this study have been deposited in the NCBI Gene Expression Omnibus under accession numbers GSE126231, GSE126734 and GSE146637 respectively for the microarray, ATAC-seq and single-cell RNA-seq. Data supporting the findings of this study are available within the article (and its Supplementary Information files). Source data behind Figures 1-4 and Extended Data Figures 1-12 are available within the manuscript files. Code availabilityCustom computer code and algorithm used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
142
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 63 publications
16
142
2
Order By: Relevance
“…After computational removal of cells from other epithelial compartments (Methods), the combined dataset allowed us to assign the basal-suprabasal border according to the sorted basal (ITGA6+) cells (Figure 2A, Methods). Notably, the previously defined intermediate with recent studies in skin as well as oral epithelia ( Figure S3D) (6,21,22). To more closely examine where the first transcriptional changes begin (signifying the onset of differentiation), we grouped the cells along the trajectory into 10 differentiation bins ( Figure 2D, S3E We found that these divisions occurred parallel to the basement membrane, producing daughter cells that were fully integrated within the basal layer and retained reporter expression ( Figure 3E and Movie S1).…”
Section: Main Textsupporting
confidence: 84%
See 2 more Smart Citations
“…After computational removal of cells from other epithelial compartments (Methods), the combined dataset allowed us to assign the basal-suprabasal border according to the sorted basal (ITGA6+) cells (Figure 2A, Methods). Notably, the previously defined intermediate with recent studies in skin as well as oral epithelia ( Figure S3D) (6,21,22). To more closely examine where the first transcriptional changes begin (signifying the onset of differentiation), we grouped the cells along the trajectory into 10 differentiation bins ( Figure 2D, S3E We found that these divisions occurred parallel to the basement membrane, producing daughter cells that were fully integrated within the basal layer and retained reporter expression ( Figure 3E and Movie S1).…”
Section: Main Textsupporting
confidence: 84%
“…Extensive efforts have been made to define the cell states and correspondent behaviors within the basal layer that fuel this lifelong tissue turnover. Several studies support a model of epidermal homeostasis through the cooperative efforts of multiple, molecularly distinct progenitor types (Figure S1B) that include fast-cycling, differentiation-primed committed progenitors underpinned by a second, molecularly distinct slow-cycling stem cell population ( 4 , 5 ), pairs of directly coupled stem and differentiation-committed progenitor cells ( 6 ), or two independent stem cell populations with different cycling kinetics and transcriptional profiles ( 7 ). In contrast, other studies instead propose a single type of proliferating progenitor population that generates dividing and differentiating cells with equal probability at the population level ( 811 ) (Figure S1B) .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings closely resembled the classic proliferative zone maps of 3D non-scaffold spheroids and the epithelial planarization patterns outlined by several investigators ( Luo et al, 2011 ; Costa et al, 2016 ). This is reminiscent of stretch-induced keratinocyte expansion patterns ( Aragona et al, 2020 ) and reveals that spheroid cultures retain spaciotemporal inclinations that direct cellular fate in culture. It is likely that epidermal stem cells are sensitive to the post-embryonic stage of the tissue of origin.…”
Section: Discussionmentioning
confidence: 87%
“…Disruption of the branched actin nucleator, Arp2/3, or its activator, the WAVE complex, perturbs epidermal function with varying effects on structure (Cohen et al, 2019;van der Kammen et al, 2017;Zhou et al, 2013). Unbranched actin filaments produced by the formin family anchor adhesions and participate in physiological adaptations to mechanical stretch within the epidermis (Aragona et al, 2020;Kobielak et al, 2004). Endogenous miRNA restricts expression of the canonical formin, Dia1, to the basal layer of human epidermis and tongue (Sundaram et al, 2013;Sundaram et al, 2017).…”
Section: Introductionmentioning
confidence: 99%